Pengaruh Pendidikan Kesehatan terhadap Perilaku Pencarian Informasi Kesehatan pada Remaja di Sekolah - Anggra Trisna Ajani (Journal on Education, 2023)
School-based health education plays a crucial role in improving health information seeking behavior among adolescents. This study aims to investigate the influence of health education on health information seeking behavior among adolescents in schools. The research methodology utilized in this study is a literature review, gathering data from reliable sources. The analysis of the literature review indicates that school-based health education has a positive impact on adolescents' knowledge of health issues and their ability to evaluate the reliability of health information sources. Furthermore, health education also influences the adoption of healthy behaviors among adolescents. However, challenges such as digital literacy need to be addressed to enable adolescents to effectively utilize health information. In conclusion, school-based health education significantly enhances health information seeking behavior among adolescents and assists them in making informed health decisions.